16S RDNA clone library analysis of soil bacteria from three different sites in Peninsula Antarctica / Tahereh Yazdani Nia - Nia, Tahereh Yazdani (2011)
Soil bacterial diversity from three locations on maritime Antarctica was analyzed using 16S rRNA gene clone library construction and restriction fragment length polymorphism (RFLP) fingerprinting. Soil samples were from near Rothera Research Station in Rothera Point from Adelaide Island, from Viking Valley on north-eastern side of Mars Glacier from Alexander Island, and from Léonie Island on northern Marguerite Bay, Antarctic Peninsula. Five hundred and forty-eight clones were screened by RFLP and representatives of each phylotype were sequenced for identification. The phylotype sequences showed close relationship (i.e. ≥95% similarity) with bacterial divisions Acidobacteria, Actinobacteria, Bacteroidetes, Chloroflexi, Cyanobacteria, Firmicutes, Gemmatimonadetes, Proteobacteria, Verrucomicrobia and Unclassified Bacteria. The least number of phylotypes were observed in Rothera Point soil sample (25) whereas the highest phylotype diversity belonged to Léonie Island (35). Certain phylotypes were exclusive to one site or two, whereas 33% of the phylotypes were shared by all clone libraries. Shannon diversity index (H’) revealed the highest bacterial diversity in Léonie Island (3.14) and lowest diversity in Rothera Point (2.93). The soil from Viking Valley showed high diversity (H’=3.09) comparable to that of the vegetated soil of Léonie Island despite the severity of its climate condition. There is an evident environmental influence on the pattern of biodiversity where the human-disturbed soil sample of Rothera Point revealed less bacterial diversity than the undisturbed soils of Léonie Island and Viking Valley.